2012
DOI: 10.1120/jacmp.v13i6.3887
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive dosimetric evaluation of using RapidArc volumetric‐modulated arc therapy for the treatment of early‐stage nasopharyngeal carcinoma

Abstract: The purpose of this study was to investigate the potential benefits of using triple‐arc volumetric‐intensity modulated arc radiotherapy (RapidArc (RA)) for the treatment of early‐stage nasopharyngeal carcinoma (NPC). A comprehensive evaluation was performed including plan quality, integral doses, and peripheral doses. Twenty cases of stage I or II NPC were selected for this study. Nine‐field sliding window IMRT, double‐arc, and triple‐arc RA treatment plans were compared with respect to target coverage, dose c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
(21 reference statements)
0
14
1
Order By: Relevance
“…Our previous study also reported better treatment efficiency and plan quality achieved using RapidArc (RA) compared to IMRT for early stage nasopharyngeal carcinoma (NPC) (2) . The study of Verbakel et al (4) showed that RA allowed much faster delivery of hypofractionated doses and generated more conformal plans than conventional stereotactic body radiotherapy (SBRT) for peripheral lung tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study also reported better treatment efficiency and plan quality achieved using RapidArc (RA) compared to IMRT for early stage nasopharyngeal carcinoma (NPC) (2) . The study of Verbakel et al (4) showed that RA allowed much faster delivery of hypofractionated doses and generated more conformal plans than conventional stereotactic body radiotherapy (SBRT) for peripheral lung tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, RapidArc (Varian Medical Systems, Palo Alto, CA) has been found to produce comparable conformal dose distributions and faster treatment delivery compared to conventional static intensity‐modulated radiotherapy (IMRT) in various treatment sites, some of which involved low‐density medium such as lung, breast, and nasopharyngeal regions (1–5) …”
Section: Introductionmentioning
confidence: 99%
“…34 Reductions of the doses to the spinal cord or brainstem could be beneficial to patients with laryngeal cancer with recurrent or locally persistent diseases, especially when a second course of treatment is necessary. 35 The thyroid is a concern in IMRT because hypothyroidism has been reported to occur in between 6% and 48% of cases. [36][37][38][39] Akgun et al 40 and Cella et al 41 recommended the thyroid volume receiving $30 Gy (V 30Gy ) as a possible predictor of hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Kan et al [32] indicated that double-arc VMAT produced slightly inferior parotid sparing than nine-field “sliding-window” IMRT. A similar result was reported by Zhang et al [28], who showed that the dose distribution of single-arc VMAT plan for NPC was slightly worse than that of a nine-field IMRT plan.…”
Section: Discussionmentioning
confidence: 99%